Simulation and Analysis of Short Channel Effects on Bulk and Tri-Gate Multiple Input Floating Gate Mosfet - Mohd Maarof, Siti Nuur Basmin (2008)
While the scaling limits of MOSFET have been widely researched, the scaling of Multiple Input Floating Gate (MIFG) MOSFET devices has been receiving less attention. The MIFG MOSFET has short channel effect that arises from the scaling of the device at a more significant level than the typical MOSFET because the existence of the floating gate electrode widens the distance of the input gates and the channel. This distance weakens the ability of the gate to control the channel charge effectively which leads to higher short channel effects. Tri-gate MIFG MOSFET proposed in this thesis is combination technologies of a MIFG MOSFET planar device structure and a 3-D Tri-gate transistor. The ability to circumvent short channel effect of the Tri-gate MOSFET are emphasized on the subthreshold characteristic of the device by monitoring the DIBL and subthreshold slope parameter and is compared with a bulk MIFG MOSFET structure at equal technology parameter. The device coupling capacitor and voltage bias at control gate are varied in order to analyze its influence on these effects. Two different structures, Top Tri-gate MIFG MOSFET and Side Tri-gate MIFG MOSFET were studied. This research focuses in the physical MIFG MOSFET structures and analyzes its short channel effect behavior by performing 3-D computer-based numerical simulations using Davinci simulator. There were two sets of results obtained when comparing the short channel effect of the two Tri-gate MIFG MOSFETs with bulk MIFG MOSFET. At C2/C1 ≤ 1 and at variable Vgate2, Tri-gate MIFG MOSFETs shows better results than the bulk MIFG MOSFET in subthreshold slope and DIBL effect with best in C2/C1 = 0.5 followed by C2/C1 = 1. From the electrostatic potential distribution graph of the devices, the better short channel effect suppression can be interpreted as a result of better gate controllability in the Tri-gate MIFG MOSFET than the bulk MIFG MOSFET channel. However, for C2/C1 > 1, overall Tri-gate MIFG MOSFETs shows worse short channel effects than the bulk MIFG MOSFET. The Tri-gate device structure shows the worst short channel effect behavior than the bulk device structure which contradicts with the previous results. The correlation between C2/C1≤1 and C2/C1>1 for a two-input gates in the Tri-gate MIFG MOSFET to control short channel effects is that gate 1 as the signal gate has to have a large area in order to control the channel effectively. At the same time, the voltage applied at gate 2 has to be controlled just to be sufficiently enough to turn on the transistor. The placement of the input gates as the top and side of the floating gate does give significant effect in the simulation results where the Top Tri-gate MIFG MOSFET gives better or approximately same data with the Side Tri-gate MIFG MOSFET.It can be concluded that the suppression of short channel effects of the Tri-gate MIFG MOSFET must not only consider the Tri-gate structure itself, but must also take into account the area of input gate coupling capacitance, voltage bias and placement of the input gates.